1996
DOI: 10.1046/j.1365-2249.1996.d01-732.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the neutralizing anti-hepatitis B surface (HBs) antibody response in vitro in HBs vaccine recipients and patients with acute or chronic hepatitis B virus (HBV) infection

Abstract: SUMMARYAntibodies directed to the HBs antigen indicate viral clearance and the development of life-long immunity in patients that recovered from HBV infection. In HBs antigen vaccine recipients anti-HBs antibodies provide protective immunity. However, little is known about the regulation of this HBsspecific antibody response. The existence of anti-HBs-secreting B cells was demonstrated using the highly sensitive ELISPOT technique compared with conventional ELISA in serum and cell culture supernatants. In the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 26 publications
(48 reference statements)
3
46
0
1
Order By: Relevance
“…Cells from 12 donors recognized 2 epitopes ( Table 2). The most vigorous T-cell responses were elicited by peptide P4 (mean SI of positive cells 27.2, range 7-55) followed by peptide P1 (mean SI of positive cells 11.6, range [7][8][9][10][11][12][13][14][15][16][17]. Experiments with PBMC subpopulations depleted of CD4 ϩ or CD8 ϩ cells showed that all T-cell responses were mediated by CD4 ϩ T-helper cells (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Cells from 12 donors recognized 2 epitopes ( Table 2). The most vigorous T-cell responses were elicited by peptide P4 (mean SI of positive cells 27.2, range 7-55) followed by peptide P1 (mean SI of positive cells 11.6, range [7][8][9][10][11][12][13][14][15][16][17]. Experiments with PBMC subpopulations depleted of CD4 ϩ or CD8 ϩ cells showed that all T-cell responses were mediated by CD4 ϩ T-helper cells (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…A defective neutralizing anti-HBs response may be related to a HBsAg-specific T-helper cell and B cell defect. 15 This immune response is expected to be worse in liver transplant recipients because of the immunosuppressive medications. Therefore, the spontaneous development of anti-HBs is most unexpected and has not been reported previously in other series of patients receiving lamivudine prophylaxis 5,7 or in whom HBIg prophylaxis was discontinued after long-term administration.…”
Section: Discussionmentioning
confidence: 99%
“…The frequencies of anti-HBs secreting B cells within peripheral blood mononuclear cells (PBMC) were determined using an anti-HBs-specific ELISPOT technique as described previously. 18 In brief, 96-well plates with high-protein binding membranes (MAIP S4510; Millipore, Eschborn, Germany) were coated overnight with recombinant HBsAg (5 mg/well) or tetanus toxoid (Chiron Behring, 2 mg/well) as irrelevant control antigen. After washing with sterile distilled water, the plates were preincubated with RPMI 1640 ϩ 3% bovine serum albumin (BSA) for 1 hour before cells were added in triplicates in 2 different concentrations (2.5 ϫ 10 5 , 1.25 ϫ 10 5 per well) and incubated overnight in a humidified atmosphere at 37°C and 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%